Ulul Azmi's Communication Patterns: Diplomatic and Transformative - Usman, Rahmalia; Abdullah, Abdullah (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study examines the communication patterns of Ulul Azmi, emphasizing their diplomatic and transformative approaches to delivering dakwah in the face of various ideological, social, and political challenges. By exploring the communication patterns of figures such as Nuh, Ibrahim, Musa, Isa, and Muhammad (SAW), this qualitative descriptive research reveals how their methods were not only persuasive but also capable of reshaping the collective consciousness and moral framework of their societies. Moreover, their strategies had a significant impact on the thought processes and social values within these communities. Employing narrative analysis of primary sources (the Qur'an and Hadith) along with academic literature, the study identifies common strategies, including patient, dialogical, and humanistic communication techniques. These approaches have been effective in promoting both spiritual awareness and sustainable societal reform. Additionally, this study confirms the ongoing relevance of Ulul Azmi's communication patterns in contemporary contexts, particularly in areas such as digital dakwah, multiculturalism, and interfaith dialogue. The findings aim to contribute to the development of an adaptable, ethically grounded framework for Islamic communication well-suited to addressing modern global challenges.